2003
DOI: 10.1093/jnci/djg018
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibody Levels at the Cervix During the Menstrual Cycle of Women Vaccinated With Human Papillomavirus 16 Virus-Like Particles

Abstract: The relatively high titer of anti-HPV16 antibodies at the cervix is promising in terms of vaccine efficacy; however, the decrease in antibody titer around ovulation raises the possibility that the HPV16 VLP vaccine might be less effective during the peri-ovulatory phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
151
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 37 publications
6
151
2
4
Order By: Relevance
“…This suggests the importance of future studies to better understand the effects of the menstrual cycle phase on antibody measurements in the periphery and cervix. We observed that OC use was not an important modifier of the degree of correlation observed between serum and cervical secretion measures, which appears to contrast with previous data from Nardelli-Haefliger et al [25]. This contradiction may be due to variations in sample size and study design, such as in the Nardelli-Haefliger et al study participants were sampled multiple times during a two month period following immunization while our correlations are only based on month 12 samples for serum and cervical secretions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This suggests the importance of future studies to better understand the effects of the menstrual cycle phase on antibody measurements in the periphery and cervix. We observed that OC use was not an important modifier of the degree of correlation observed between serum and cervical secretion measures, which appears to contrast with previous data from Nardelli-Haefliger et al [25]. This contradiction may be due to variations in sample size and study design, such as in the Nardelli-Haefliger et al study participants were sampled multiple times during a two month period following immunization while our correlations are only based on month 12 samples for serum and cervical secretions.…”
Section: Discussioncontrasting
confidence: 99%
“…A study performed by Nardelli-Haefliger et al examined levels of anti-HPV16 antibody at the cervix following vaccination and found that cervical HPV16 type-specific antibodies range from 0.5-50% of systemic levels [25]. It is currently unclear whether systemic measures of post-vaccination immunity can serve as a good surrogate for local levels of immune protection at the cervix.…”
Section: Introductionmentioning
confidence: 99%
“…In cell cultures, oestrogen interacts with adhesion molecules, producing increased deformability and contraction, which theoretically could facilitate cellular exfoliation (Gorodeski, 1998). Finally, levels of immunoglobulins in cervical secretions reach their nadir at mid-cycle, which may favour HPV replication and accumulation to high viral loads (Franklin and Kutteh, 1999;Nardelli-Haefliger et al, 2003). The explanation for the observed, more minor spike in viral load around the time of menses is also unexplained, although apoptosis secondary to oestrogen withdrawal represents a possible explanation (Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2). In addition to the IgG antibodies that are transudating through mucosal membranes, and, thus are found at the uterine cervix 25 also IgA are expected to be beneficial for HPV-specific protection. Although antibody titers may fall during ovulation, clinical studies with VLP have shown efficient and continuous protection.…”
Section: Discussionmentioning
confidence: 99%